PENGEMBANGAN INSTRUMEN PENILAIAN KETERAMPILAN PROSES SAINS TERINTEGRASI 4C PADA PEMBELAJARAN BIOLOGI SMA - Yunita Wardianti; Yuni Krisnawati; Endang Suswati (Jurnal Perspektif Pendidikan, 2023)
This study aimed to determine the development process, validity, reliability, and practicality of the 4C integrated science process skills assessment instrument in high school biology learning. This research was a type of development research with development steps including determining the purpose of preparing the instrument, looking for relevant theory or scope of material, compiling instrument item indicators, compiling instrument items, content validation, revising based on validator input, conducting tests on appropriate responses to obtain response data participants, perform validity and reliability analyses, and assemble the instrument. The subjects in this study were class X students of SMA Negeri 4 Lubuklinggau City. Data analysis was performed by analyzing content validity using the Aiken index formula, construction validity using exploratory factor analysis (EFA), and reliability using Cronbach's alpha formula. The results of this study were that the 4C integrated science process skill assessment instrument in high school biology learning which was developed was valid with an Aiken V index value of 0.87 and was included in the high category, and the developed instrument contains aspects that are feasible to use which were included in 4 factors. The instrument for assessing the 4C integrated science process skills in high school biology learning was developed to be reliable with a reliability coefficient of 0.729. The 4C integrated science process skills assessment instrument for high school biology learning was developed practically with a practical value of 85.23% which was included in the very practical category.